3D Electrical Study of Seawater Intrusion within the Superficial Aquifer in Damsarkho Region - الشامي عفراء; محمد بعلة; عمر جعفر (Latakia University Journal -Basic Sciences Series, 2022)
The intrusion of seawater with groundwater in the study area was diagnosed by determining the concentrations of chlorine and sodium and calculating the salinity basis of electrical conductivity measurements of water samples taken from wells in the region. To determine the locations of electrical sounding we have based on the results of chemical measurements. We have affected 31 sounding points distributed along five profiles vertical to the shore line. In this study we used the vertical electrical sounding of resistivity (Schlumberger array), the 1D interpretation of electrical measurements were processed using the IPI2Win program, on the basis of 1D interpretation we built the three-dimensional geoelectric model using the RockWorks program. The result of the chemical study showed rising in salinity values of the water samples close to the shore line and the samples relatively far due to the high pumping rate, where the salinity values in these samples exceeded 1000 mg/l, the high salinity was accompanied by an increase in the concentration of chlorine ion to exceed 250 mg/L and an increase in the concentration of sodium ion where it exceeded 200 mg/L, so that the water of these wells is mostly unfit for drinking and irrigation. The geochemical Na/Cl ratio indicated the effect of seawater on the salinity of groundwater, where this ratio did not exceed 0.86, while the value exceeded 0.86 in wells where the concentration of sodium exceeds that of chlorine due to the presence of factors that led to an increase in sodium ion, such as the use of pesticides and chemical fertilizers, Pollution with sewage water in addition to pollution with sea water. The three-dimensional modeling process showed that the vertical development of the seawater process towards land may reach an average distance of 950 m, compared with the previous studies the intrusion belt degradation about (450-850m) as the results of using irrigation channels. In addition, the rise of the intrusion belt increases towards the north due to the intense pumping and increases depth towards the east, reaching its maximum depth 25 m.